Desain Pembelajaran Berbasis ICT untuk Pengembangan Spirituality-Based Learning dalam Meningkatkan Karakter dan Kesadaran Spiritual Peserta Didik - Queen Qonita; Muhammad Miftah Gunawan; Riris Eka Setiani (Lembaga Yasin AlSys, 2026)
The development of Information and Communication Technology (ICT) has driven a transformation in the learning paradigm toward a more flexible, interactive, and learner-centered system. However, the acceleration of educational digitalization also presents challenges in the form of a weakening of students’ spiritual, moral, and character dimensions due to the dominance of technology use that tends to be oriented toward cognitive aspects. This study aims to analyze the concept, implementation, and implications of ICT-based learning design in the development of Spirituality-Based Learning to improve students’ character and spiritual awareness. This study uses a qualitative approach with a library research method through the examination of journal articles, books, and scientific documents relevant to ICT-based learning, spirituality in education, Islamic education, and 21st-century competencies. The results of the study show that the integration of ICT with Spirituality-Based Learning can be realized through the components of meaningful learning, reflective learning, value internalization, spiritual connectedness, and ethical digital engagement. The implementation of this model contributes to strengthening the values of sincerity, trustworthiness, justice, and responsibility, while also improving digital literacy, critical thinking skills, religious character, and students’ spiritual awareness. The conclusion of this study affirms that ICT-based learning design integrated with spirituality is a strategic alternative for realizing Islamic education that is holistic, adaptive, and relevant to 21st-century needs. The implications of this study provide a conceptual basis for educators and Islamic educational institutions in designing digital learning that emphasizes not only cognitive competence but also the formation of students’ character and spiritual awareness.